THE EFFICIENCY OF COOPERATION TYPES OF TRANSPORT ON BASE OF AIR TRANSPORTATION «OPEN JAW» - Бугайко, Д.О.; Чепурна, А.В. (Science-based technologies, 2009)
The classification of methods increasing the competitiveness of airlines is reviewed and the method of interaction air carriers with other modes of transport are investigated in the article; the algorithm for constructing transport cooperation, which is based on the «Open Jaw» air transportation, and the main advantages and disadvantages of this method were worked out.